Analisis Kesesuaian Lahan untuk Tanaman Jagung Menggunakan Citra Landsat 8 OLI/TIRS dan Sistem Informasi Geografis di Kabupaten Lampung Selatan - Ridwan, Ridwan; Amin, Muhammad; Asmara, Sandi; Andini, Tiara (Jurnal Agricultural Biosystem Engineering, 2023)
Analysis of land suitability for corn plants is needed to increase production in the development of the agricultural sector. South Lampung Regency is the largest corn producer in Lampung Province with production reaching 598,032 tonnes in 2016. The aim of the study was to determine the potential for land development for corn plants using Landsat 8 OLI/TIRS image interpretation and Geographic Information Systems in South Lampung Regency by assessing the quality of the land and to determine the level of land suitability conditions for corn crops based on planting seasons 1, 2 and 3 in South Lampung Regency. The analysis is carried out by the matching method or by giving a class assessment to each of the required parameters. The results show that the 1st planting season has the greatest level of land suitability compared to the other growing seasons, 73% very suitable to suitable. Meanwhile, Planting Season 2 had the lowest suitability level of 60% due to less stable temperatures due to the transition from rainy to dry seasons. And Planting Season 3 has a moderate suitability level of 66%, because this season the temperature has stabilized for cultivating corn. Keywords: Corn, Geographic Information System, Class Assessment, Land Suitability, Landsat 8 OLI/TIRS Imagery, Matching.